Design and Motion Control of a 2-DoF Exoskeleton Robot for Ankle Joint Rehabilitation of Post-Stroke Patients - Abryandoko, Eko Wahyu; Ashari, Faisal (Engineering, Technology & Applied Science Research, 2025)
Post-stroke patients often experience motor function impairments in the lower extremities, including the ankle joint, which can hinder walking ability and body balance. Rehabilitation plays a crucial role in restoring these functions; however, it typically requires a lengthy process and intensive involvement from medical professionals. This study aims to design and develop a Two-Degree-of-Freedom (2-DoF) ankle exoskeleton system, incorporating dorsiflexion–plantarflexion and inversion–eversion movements, as an alternative automated and programmable rehabilitation therapy. The system’s performance was evaluated by comparing the actual joint movement angles with reference angles set through preset inputs. Tests were conducted under both unloaded conditions and loaded conditions simulating the limb mass of users. The results showed that for dorsiflexion–plantarflexion movements, the average angle error was 1.9° under unloaded conditions, increasing to 2.7° when a load was applied. For inversion–eversion movements, the average error was 2.4° without load and 3.2° with load. The system demonstrated operational stability and consistency in following the programmed motion trajectories. Based on these findings, the developed exoskeleton has potential as an effective, safe, and efficient rehabilitation therapy device to support functional recovery in post-stroke patients.